Swamp eel (Monopterus albus) (MULTIMEDIA) - Sofiah Mohammad Salleh (2004., 2004)
This multimedia module presents the information on swamp eel or locally known as "belut sawah". This module is developed for first year students taking courses in animal biodiversity, researchers, and fish covers. The softwares used to develop this product are marcomedia Authorware 6.5®, besides Adobe Photoshop 7®, Adobe Illustrator 10®, Ulead COOL 3D®, Microsoft PowerPoint® and Nero Express®. The users of this midule will be exposed to "belut sawah" in detail with some original pictures. At the end of this midule the quiz section is provided for the users to assess their understanding and cimprehension on the subject matters by answering the questions given. Hopefully, this midule can provide good and detail information on swamp eel.
Project paper (B.S. cum Ed. (Hons)) - Universiti Putra Malaysia, 2004.